230k views
0 votes

g(x) = 3x - 6and


{g}^( - 1)(x) = (x + 6)/(3). With g(x) and

{g}^( - 1)(x), find

{g}^( - 1)(g(10)). Make sure to show your work.​

User Kazinov
by
5.8k points

1 Answer

1 vote

Hey there! :)

Answer:


g^(-1) (g(10))=10

Explanation:

Begin by calculating g(10):

g(x) = 3x - 6

Substitute in 10 for x:

g(10) = 3(10) - 6

g(10) = 30-6

g(10) = 24.

Plug '24' into 'x' into
g^(-1) (x)


g^(-1) (24)=((24) + 6)/(3)

Simplify:


g^(-1) (24)=(30)/(3)


g^(-1) (24)=10

User Orionis
by
6.0k points